Heavy metals content in Pahang river stream sediment : upper and lower baseline studies - Nur Syarmim , Mohamed Noor (2012)
Stream sediment has an important role in the essential nutrients cycle of aquatic environments as well as in the transport of the nutrients and pollutants. Human activities, such as mining, farming, logging, and industrialization, may adversely affect stream sediment quality. These activities can cause heavy metals toxic pollutant that can be dangerous to the environment. The present study was carried out to determine concentrations of heavy metals content in the upper and lower river stream sediments of Pahang River. Three sampling sites were chosen from upper which are in Sungai Tembeling, Sungai Jelai and Temerloh and three sampling sites for lower regions which are Kampung Belimbing, Kampung Temai and Pekan at Pahang River. These samples were analyzed using Atomic Absorption Spectrometry (AAS) to determine the concentration of heavy metals in sediment. The observed stream sediment heavy metals contamination is further evaluated which is higher concentration of heavy metals contamination is in lower Pahang River than upper region.